DISCUSSIONS ON THE TOPIC OF EDUCATION AND CURRICULUM AND ASPECTS INVOLVING IT (REMUNOM, 2024)
The general objective of the current research was to promote discussions on the topic of Education and Curriculum and related aspects. The methodological procedure involved a qualitative bibliographical study, which was analyzed using content analysis. The results show that the curriculum goes beyond a simple list of content to be learned, serving as a path for implementing pedagogical actions and involving power relations, as well as cultural, social, and political issues. The implementation of an integrated curriculum is essential to promote interdisciplinarity and communication between different areas of knowledge, aiming at a global understanding and the development of critical and creative skills. The BNCC guides the construction of curricula, while methodologies, formative assessments, and effective planning are essential for quality teaching. The dynamics between teacher and student are also an issue within the curriculum and should be based on respect and ethics, moving away from authoritarian practices. Finally, there are three curriculum theories: traditional theory, critical theory, and post-critical theory. Furthermore, the curriculum can be represented by different approaches (multidisciplinary, pluridisciplinary, interdisciplinary and transdisciplinary) and its manifestations vary between formal, real and hidden.